Penerapan Trainer Media Pembelajaran Sistem Pembangkit Listrik Tenaga Surya Dalam Pengukuran Arus Dan Tegangan Listrik Pada Rangkaian Seri Paralel: Penerapan Trainer Media Pembelajaran Sistem Pembangkit Listrik Tenaga Surya Dalam Pengukuran Arus Dan Tegangan Listrik Pada Rangkaian Seri Paralel - I Putu Suka Arsa (Jurnal Pendidikan Teknik Elektro Undiksha, 2021)
This research aims to create and develop learning media for solar power plants in electrical engineering education study programs at Ganesha University of Education that can be used to support the learning process so that it makes it easier for employers to deliver material related to solar power plants. This learning medium combines the main components of a solar power plant so that it gives students the opportunity to assemble a solar power plant in a simple way. The method used in this research is research and development. The study used a questionnaire as a reference in data collection which was filled in directly by content experts, media experts and electrical engineering education students as respondents, from the results of validation test content experts obtained a proportion of 95.83% with a very feasible classification, validation tests from media experts obtained a proportion of 97 .82% with a very appropriate classification, the results of the small group validation test with 5 students as respondents obtained an average score above 40 and the proportion of 100% with a very high category, a large group validation test with 10 students as respondents obtained an average score above 44 and the proportion of 100% is in the very high category. Based on the results of validation tests from experts and also student trainers for solar power plants that are suitable for use in supporting the learning process in electrical engineering education study programs,